Effects of foam mat-drying condition on physicochemical and antioxidant properties of instant Physalis angulata L. enriched with Moringa oleifera L. extract - Widhanti, Ajeng; Iwansyah, Ade Chandra; Yelliantty, .; Taufik, Kurniawan; Pramareti, Gradia Martin Jati; Indriati, Ashri; Hazrulrizawati, Abd Hamid (SciELO Brazil, 2024)
Food drying is still a crucial step in the food manufacturing process for food preservation, and the foam-mat drying method can be utilized to further enhance food preservation. This study aims to develop an instant L. powder enriched with Moringa oleifera L. extract and to evaluate the effect of foam mat drying conditions on physicochemical and antioxidant properties.The experimental design used a factorial completely randomized block design (FCBD), with triplicates. Based on the results showed that the interaction between the different forms of moringa extract, when added, and drying temperature affected color, water activity, bulk density, hygroscopicity, total acid titration, moisture content, ABTS, antioxidant activity and total flavonoid contents (p<0.05) but did not affect solubility, total soluble solids, flow rate, pH, DPPH antioxidant activity and total phenolic contents (p>0.05). Samples dried at a temperature of 70°C (T3), both liquid (F1) and microencapsulated (F2), exhibited the best physicochemical and antioxidant properties. These findings confirmed the suitability of foam mat drying to produce P. angulata instant powder enriched with M. oleifera extract for functional food ingredients.